Bouve, C. (2010). L’utopie des crèches françaises au 19e siècle: un pari sur l’enfant pauvre. Essai socio-historique. Bern: Lang, Exploration. 294 p. - Périsset, Danièle (Swiss Journal of Educational Research, 2013)
Recension